Learning Strategies at Muhammadiyah 1 Taman Sidoarjo During Pandemic Covid 19 - Harits Arba Amrullah (Proceedings of The ICECRS, 2021)
The purpose of this study was to analyze the effectiveness of implementing the learning from home (BDR) process during the Covid-19 pandemic at SMK Muhammadiyah 1 Taman. This study uses a qualitative method. The data collection technique used is a questionnaire given to students once a month. The subjects of this study were students of SMK Muhammadiyah 1 Taman. Based on the results of research conducted by filling out questionnaires, in general the implementation of home learning (BDR) for SMK Muhammadiyah 1 Taman students is quite effective with a percentage of 60-79%. The results of the questionnaire on the implementation of BDR learning that have poor effectiveness with 48% criteria are in the evaluation process. It is recommended that in learning from home (BDR), teachers are able to design learning activities from planning to evaluation in a simpler, more creative and effective way. Keywords: Covid-19, Access to Learning, Learning from Home.